O idiomatismo composicional de Juarez Moreira no álbum Riva e transcrição comentada de 04 peças - Gustavo Frederico Bracher e Silva (2018)
This research studies the idiomatic music composition of Juarez Moreira, focusing on the analysis and transcription of four solos acoustic guitar pieces from the album RIVA: “Conversa Comigo Mesmo”, “Valsa Para Maria”, “Samblues” and “Riva”. The text is divided into four parts. The first part consists of a small biography that seeks to contextualize the composer in the Brazilian musical scene, based on factors such as origin, musical background, career path and compositional work. The second part aims to discuss the concept of the term “idiomatic” in the musical context, mainly within the acoustic guitar literature and in the Brazilian acoustic guitar tradition, as well as its presence in the production of Juarez Moreira. The third part studies the transcription process of popular music works, such as the problems encountered in order to seek a greater fidelity to the compositional thinking. The fourth part presents the comments and the analysis of the works “Riva”, “Valsa Para Maria”, “Samblues” and “Conversa Comigo Mesmo” from the album RIVA. The annexes consist of the transcripted scores of the repertoire analyzed according to the criteria studied in this work.